2023
DOI: 10.3389/fnins.2023.1156308
|View full text |Cite
|
Sign up to set email alerts
|

Acupuncture and other traditional Chinese medicine therapies in the treatment of children’s tic syndrome: A network meta-analysis

Abstract: BackgroundTic disorders (TD) are a kind of neuropsychiatric disease that frequently occur among preschool and school-age children, mainly characterized by motor tics or sometimes accompanied by vocal tics, and its pathogenesis is still unclear. The clinical manifestations are mainly characterized by chronic multiple movements, rapid muscle twitching, involuntary occurrence, and language disorder. Acupuncture, tuina, traditional Chinese medicine, and other methods are commonly used in clinical treatments, which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…In a previous study, acupuncture was shown to influence neuroendocrine homeostasis by modulating the vagus nerve, effectively addressing both hypertension and insomnia ( 42 ). Additionally, acupuncture has been found to enhance the levels of certain sleep-related neurotransmitters, such as serotonin and gamma-aminobutyric acid, while decreasing sleep-inhibitory neurotransmitters, like norepinephrine, in the brain ( 38 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a previous study, acupuncture was shown to influence neuroendocrine homeostasis by modulating the vagus nerve, effectively addressing both hypertension and insomnia ( 42 ). Additionally, acupuncture has been found to enhance the levels of certain sleep-related neurotransmitters, such as serotonin and gamma-aminobutyric acid, while decreasing sleep-inhibitory neurotransmitters, like norepinephrine, in the brain ( 38 ).…”
Section: Discussionmentioning
confidence: 99%
“…Acupuncture, a traditional Chinese medicinal treatment, is widely used in clinical practice worldwide as a traditional Chinese medicine (TCM) intervention (34)(35)(36). Previous research has provided evidence of acupuncture's influence on the nervous system (37,38). Investigations have also delved into the molecular mechanisms underlying acupuncture's impact on the nervous system (39).…”
Section: Discussionmentioning
confidence: 99%
“…For example, within the realms of diabetes and neurological disorders, acupuncture exhibits remarkable advantages (33)(34)(35)(36). Network meta-analyses have previously explored traditional Chinese medicine interventions, including acupuncture (37). In 2023, a scoping review of systematic reviews and meta-analyses was conducted to assess the effectiveness of acupuncture as a treatment for cancer-related pain (38).…”
Section: Discussionmentioning
confidence: 99%
“…In animal studies focusing on polycystic ovary syndrome, liver fibrosis, colitis, intracerebral hemorrhage, and Parkinson’s disease, the combined approach seems to improve treatment effectiveness and outcomes more than each therapy alone [ 48 52 ]. In clinical studies, the synergistic application of acupuncture and herbal medicine has significantly enhanced outcomes for conditions such as tic syndrome and cerebral palsy by improving both physical and cognitive function [ 16 , 17 ]. While the exact mechanisms of how acupuncture and herbal medicine work together are not fully understood, this emerging evidence supports further investigation of these therapies as combined treatments.…”
Section: Discussionmentioning
confidence: 99%
“…For example, evidence indicates that this integrative approach improves chronic conditions, such as chronic prostatitis [ 13 ], and modulates metabolic disorders, such as gouty arthritis and atopic dermatitis [ 14 , 15 ]. In pediatrics, the combination of herbal medicine and acupuncture has also shown substantial benefits for conditions such as tic syndrome and cerebral palsy, improving both physical and cognitive function [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%